Effects of Pleistocene glaciations and rivers on the population structure of Bornean orangutans (Pongo pygmaeus) - Arora, Natasha; Nater, Alexander; van Schaik, Carel P.; Willems, Erik P.; van Noordwijk, Maria A.; Goossens, Benoit; Morf, Nadja; Bastian, Meredith; Knott, Cheryl; Morrogh-Bernard, Helen; Kuze, Noko; Kanamori, Tomoko; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Sundaland, a tropical hotspot of biodiversity comprising Borneo and Sumatra among other islands, the Malay Peninsula, and a shallow sea, has been subject to dramatic environmental processes. Thus, it presents an ideal opportunity to investigate the role of environmental mechanisms in shaping species distribution and diversity. We investigated the population structure and underlying mechanisms of an insular endemic, the Bornean orangutan (Pongo pygmaeus). Phylogenetic reconstructions based on mtDNA sequences from 211 wild orangutans covering the entire range of the species indicate an unexpectedly recent common ancestor of Bornean orangutans 176 ka (95% highest posterior density, 72–322 ka), pointing to a Pleistocene refugium. High mtDNA differentiation among populations and rare haplotype sharing is consistent with a pattern of strong female philopatry. This is corroborated by isolation by distance tests, which show a significant correlation between mtDNA divergence and distance and a strong effect of rivers as barriers for female movement. Both frequency-based and Bayesian clustering analyses using as many as 25 nuclear microsatellite loci revealed a significant separation among all populations, as well as a small degree of male-mediated gene flow. This study highlights the unique effects of environmental and biological features on the evolutionary history of Bornean orangutans, a highly endangered species particularly vulnerable to future climate and anthropogenic change as an insular endemic.